2011
DOI: 10.1590/s0004-27302011000400001
|View full text |Cite
|
Sign up to set email alerts
|

The role of uncoupling protein 2 (UCP2) on the development of type 2 diabetes mellitus and its chronic complications

Abstract: SUMMARYIt is well established that genetic factors play an important role in the development of type 2 diabetes mellitus (DM2) and its chronic complications, and that genetically susceptible subjects can develop the disease after being exposed to environmental risk factors. Therefore, great efforts have been made to identify genes associated with DM2. Uncoupling protein 2 (UCP2) is expressed in several tissues, and acts in the protection against oxidative stress; in the negative regulation of insulin secretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 62 publications
0
72
0
Order By: Relevance
“…It has been demonstrated that ''mild uncoupling'' of the mitochondrial respiratory chain due to UCP2 activity allows a more rapid flux of electrons through the mitochondrial inner membrane, reducing membrane potential and decreasing ROS production. 28 Hence, UCP2 may play a protective role in the pathogenesis of DM and its complications. Chuang et al 29 show that upregulation of mitochondrial UCP2 expression decreased ROS overproduction, leading to amelioration of apoptotic neuronal cell death in the hippocampus following status epilepticus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that ''mild uncoupling'' of the mitochondrial respiratory chain due to UCP2 activity allows a more rapid flux of electrons through the mitochondrial inner membrane, reducing membrane potential and decreasing ROS production. 28 Hence, UCP2 may play a protective role in the pathogenesis of DM and its complications. Chuang et al 29 show that upregulation of mitochondrial UCP2 expression decreased ROS overproduction, leading to amelioration of apoptotic neuronal cell death in the hippocampus following status epilepticus.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upregulation of UCP2, which has been detected in type 2 diabetes mellitus, may be linked to the proteosome system dysfunction [63,307]. Physiological role and regulation of UCP3 and UCP2, which is particularly highly expressed in the pancreatic b-cells in type 2 diabetes mellitus, have been discussed in the several recent reviews [308][309][310][311].…”
Section: Ucp Activity and Its Regulationmentioning
confidence: 99%
“…The UCP gene family is comprised of five homologous genes (UCP1 to UCP5) that encode for mitochondrial protein carriers, which promote net translocation of protons from the inter-membrane space, across the inner mitochondrial membrane to the mitochondrial matrix. This dissipates the potential energy available for the conversion of ADP to ATP and decreases ATP production (Souza et al, 2011). These genes have been shown to be involved in energy expenditure, and glucose and lipid oxidation (Dulloo and Samec, 2000;Souza et al, 2011), all of which contribute to the regulation of body weight.…”
Section: Introductionmentioning
confidence: 99%
“…This dissipates the potential energy available for the conversion of ADP to ATP and decreases ATP production (Souza et al, 2011). These genes have been shown to be involved in energy expenditure, and glucose and lipid oxidation (Dulloo and Samec, 2000;Souza et al, 2011), all of which contribute to the regulation of body weight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation